Understanding Beschikking, Regeling and Beleidsregel in Indonesian Legal System - Sholahuddin Al-Fatih; Mujibur Rahman Khairul Muluk (Audito Comparative Law Journal (ACLJ), 2023)
This article examines beschikking, regeling, and beleidseregel in the Indonesian legal system. This article aims to understand beschikking, regeling, and beleidseregel in the context of its content's type, form, and material. Using a conceptual approach method, this article will likely provide an understanding for academics and practitioners in the field of legislation. The results of this study show that beschikking in Indonesia appears in the form of KTUN. In contrast, regeling appears in the form of laws and regulations, while beleidseregel manifests in circulars and instructions. Measuring the marketability, binding, and usability of a beschikking, regeling, and beleidseregel uses a typology approach to the division of power.